Higher Education Reform is the Way to American Students Success - Kozmenko, Olena (Pedagogical Discourse, 2020)
The problem of reforms in US higher education in order to improve the student success is discussed in this article. Over the last twenty years, educators and policy makers have turned their attention to learning effectiveness, graduation rates and college completion. Higher education establishments, especially community colleges are not well organized to promote student success. They usually operate on a self-service or «cafeteria»model, allowing students to choose from an abundance of disconnected courses, programs, and support services. Such cafeteria organization creates problems in three areas: the structure of college-level programs, the intake process and student supports, and developmental education. Recognizing the importance of overcoming these problems, the process of improving higher education begins at the end of the twentieth century. In 1990 the College Tech Prep program, supported by the Carl D. Perkins Vocational and Applied Technology Act introduced the idea to provide purposeful support to students during their studies. In 2004, the Dream Achievement: Community College project proposed to overcome barriers to student success. An analysis of these reforms shows that they were narrowly targeted reforms, that have a limited effect on student success. They either treat too few people or are limited to one segment of the student experience. In contrast, the comprehensive model, which fundamentally based on the integration of a set of coordinated reforms appeared in 2013. It was the guided pathways model, which presents courses in the context of highly structured, educationally coherent program maps that align with students’goals for careers and further education. The main purpose of this model is to support students throughout their college career by helping them choose a program, enter the program, complete the program, and make a successful transition to subsequent education or employment. The task of institutions is to monitor students’progress, use evidence on student progress and program effectiveness to improve graduation rates, as well as give frequent feedback and support as needed is. .